2002
DOI: 10.1104/pp.010579
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-Stimulated Changes in Auxin and Invertase Gene Expression in Maize Pulvinal Cells

Abstract: (A.M.R., G.K.M.) Maize (Zea mays) stem gravitropism involves differential elongation of cells within a highly specialized region, the stem internodal pulvinus. In the present study, we investigated factors that control gravitropic responses in this system. In the graviresponding pulvinus, hexose sugars (d-Glc and d-Fru) accumulated asymmetrically across the pulvinus. This correlated well with an asymmetric increase in acid invertase activity across the pulvinus. Northern analyses revealed asymmetric inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 52 publications
1
18
0
1
Order By: Relevance
“…Identically, invertase activity needs to be tightly regulated in vivo to ensure ordered plant development and adaptation in various biotic and abiotic stresses (Roitsch and Gonzalez 2004;Huang et al 2007). Extensive research on invertase regulation has focused on the transcriptional level (Long et al 2002;Eason et al 2007;Proels and Roitsch 2009). However, emerging evidences indicate that invertase activity may be subject to posttranslational suppression by its inhibitory protein (Greiner et al 1999;Bonfig et al 2007;Jin et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Identically, invertase activity needs to be tightly regulated in vivo to ensure ordered plant development and adaptation in various biotic and abiotic stresses (Roitsch and Gonzalez 2004;Huang et al 2007). Extensive research on invertase regulation has focused on the transcriptional level (Long et al 2002;Eason et al 2007;Proels and Roitsch 2009). However, emerging evidences indicate that invertase activity may be subject to posttranslational suppression by its inhibitory protein (Greiner et al 1999;Bonfig et al 2007;Jin et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…1995; Philippar et al . 1999; Long et al . 2002), but a unilateral redirection of basipetal auxin transport does not provide a mechanism as it does in the root, rather auxin is likely to be redistributed at multiple positions along the shoot axis.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the effects of gravity on gene expression although there is indirect evidence suggesting that the expression of certain genes like Aux-regulated RNAs and the permease-like regulator AUX1 may be regulated by gravity (McClure and Guilfoyle 1989;Bennett et al 1996). Consideration of gravity per se as a physical stimulus that may influence gene expression is increasing (Reddy et al 1998;Davies et al 1999;Fujii et al 2000;Bao et al 2001;Link et al 2001;Long et al 2002). Using transgenic Arabidopsis plants expressing the alcohol dehydrogenase (Adh) gene promoter linked to a b-glucuronidase reporter gene (GUS), Paul et al (2001) have shown that spaceflight affects stress-signal perception.…”
Section: Introductionmentioning
confidence: 95%